The Effect of Deep Breathing Exercise Therapy Combination of Aromatherapy Based on Orem's Self Care Theory on Fatigue and Sleep Quality in Chronic Kidney Disease Patients Hemodialysis - Elok Tamarah; Umdatus Soleha; Wesiana Heris Santy; Siti Nur Hasina (GLOBAL HEALTH SCIENCE GROUP, 2025)
Patients hemodialysis with experience complaints of anemia, fatigue, sleep disturbances, and increased urea levels. Fatigue and sleep disorders are still a high problem in Indonesia. Increased urea levels can cause decreased appetite, poor nutritional intake and complaints of fatigue. The aim of the research was to analyze the effect of deep breathing exercise therapy combined with Orem self-care based aromatherapy on fatigue levels and sleep quality. The design in this research is quasi-experimental. Population of all hemodialysis patients at RSI Jemursari Surabaya. The sample size was 40 people, divided into 2 groups, namely the intervention group and the control group. The sampling technique was taken using a total sampling technique. Data were analyzed using the independent t-test a < 0.05 and looking at the difference in values using the delta test. The results of research conducted at RSI Jemursari Surabaya, showed that the average fatigue score in the intervention group before giving deep breathing exercise therapy, a combination of aromatherapy based on self-care Orem, was 36.90 and after being given the intervention, it was found to decrease by 15.90, while the control group did not. given any therapy, according to hospital standards of 34.65 and experienced a decrease of 19.65. Based on the independent t - test, it shows p = 0.003 and sleep quality shows p = 0.001, which means that deep breathing exercise therapy combined with aromatherapy based on Orem self-care has an effect on fatigue and sleep quality. Deep breathing exercise therapy a combination of aromatherapy based on Self-Care Orem according to standards, can reduce fatigue levels and improve sleep quality.